Does Compliance with Basel Core Principles Bring Any Measurable Benefits? - Podpiera, Richard (IMF Working Papers; Working Paper, 2004)
We explore the relationship between banking sector performance and the quality of regulation and supervision as measured by compliance with the Basel Core Principles for Effective Banking Supervision (BCP). Using BCP assessment results for 65 countries and 1998-2002 panel data for other variables, we find a significant positive impact of higher compliance with BCP on banking sector performance, as measured by nonperforming loans and net interest margin, after controlling for the level of development of the economy and the financial system and macroeconomic and structural factors.